2005
DOI: 10.1002/eqe.448
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental system retrofit considerations for braced steel bridge piers

Abstract: SUMMARYBraced piers of steel truss bridges having braces with latticed built-up cross-sections may su er significant damage during earthquakes due to the buckling, rapid strength degradation, and fracture of the braces. One retroÿt alternative for such a bridge pier is to supplement the existing structural system with a system of energy dissipation devices (or structural fuses) that will yield and dissipate energy prior to existing brace buckling. These devices depend on the global shear displacements of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Links with e ≤ 1.6 (M p /V p ) will yield primarily in shear and are denoted "shear links"; links with e ≥ 2.6 (M p /V p ) will yield primarily in flexure and are denoted "flexural links"; links with lengths between those bounds will yield in a combination of shear and flexure and are denoted "intermediate links." Note that Berman and Bruneau (2005) derived expressions for shear and flexural strength that accounted for shear-flexural interaction. However, test results reported in Berman and Bruneau (2006) showed that even intermediate links were able to simultaneously achieve both their plastic shear and flexural strengths due to strain hardening.…”
Section: Link Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Links with e ≤ 1.6 (M p /V p ) will yield primarily in shear and are denoted "shear links"; links with e ≥ 2.6 (M p /V p ) will yield primarily in flexure and are denoted "flexural links"; links with lengths between those bounds will yield in a combination of shear and flexure and are denoted "intermediate links." Note that Berman and Bruneau (2005) derived expressions for shear and flexural strength that accounted for shear-flexural interaction. However, test results reported in Berman and Bruneau (2006) showed that even intermediate links were able to simultaneously achieve both their plastic shear and flexural strengths due to strain hardening.…”
Section: Link Strengthmentioning
confidence: 99%
“…Note that Berman and Bruneau (2005) derived expressions for shear and flexural strength that accounted for shear-flexural interaction. However, test results reported in Berman and Bruneau (2006) showed that even intermediate links were able to simultaneously achieve both their plastic shear and flexural strengths due to strain hardening. Similar observations were made for I-shaped links by Roeder and Popov (1978) and Kasai and Popov (1986).…”
Section: Link Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, equipping VSLs into the structure is not exclusive to buildings only, but it can be also used in bridges as well. The seismic behavior improvement of bridges with VSLs was investigated previously [23], [24].…”
Section: Introduction Historical Backgroundmentioning
confidence: 99%
“…Such selfstabilizing links would also be useful in buildings where lateral bracing may not be feasible or easily provided. Furthermore, the design of EBF's to protect existing bridge pier bracing members may be employed using the approach in Berman and Bruneau (2005a), or EBF systems may be used to replace existing deficient pier brace systems.…”
Section: Introductionmentioning
confidence: 99%